Complications and objective outcomes of uterine preserving surgeries for the repair of pelvic organ prolapse versus procedures removing the Uterus, a systematic review. (December 2021) - Azadi, Ali; Marchand, Greg; Masoud, Ahmed Taher; Sainz, Katelyn; Govindan, Malini; Ware, Kelly; King, Alexa; Ruther, Stacy; Brazil, Giovanna; Calteux, Nicolas; Ulibarri, Hollie; Parise, Julia; et al.
Abstract: Background: Several authors have recently compared the outcomes and complications of surgical procedures that preserve or remove the uterus in the treatment of pelvic organ prolapse (POP) and stress urinary incontinence (SUI). Following the publication of several high quality randomized control trials on this topic we performed a new systematic review and meta analysis of this data. Methods: We performed a systematic literature search in ClinicalTrials.gov, PubMed, Scopus, Ovid, EBSCO host, Science Direct, Web of Science, and Cochrane CENTRAL for randomized controlled and cohort trials of uterine sparing prolapse repair (hysteropexy) versus hysterectomy with suspension. A total of 1285 patients from 14 studies were included in our systematic review and meta -analysis. Results: Uterine sparing procedures (hysteropexy) were comparable to hysterectomy with suspension for recurrence rates (RR = 0.908, 95% CI [0.385, 2.143]), reoperation rates (RR = 1.517, 95% CI [0.802, 2.868]), length of hospital stay, (SMD =  − 0.159 days, 95% CI [−0.375, 0.057]), voiding dysfunction (RR = 1.089, 95% CI [0.695, 1.706]), and intraoperative blood loss (SMD =  − 0.339, 95% CI [−0.631, 0.047]). However, hysteropexy had shorter operative time than hysterectomy with suspension (SMD =  − 1.191 h, 95% CI [−1.836, −0.545]), and fewer visceral injuries (RR = 0.421, 95% CI [0.244, 0.725]). Conclusion: We found no significant differences in the outcomes or major complications of uterine preserving surgical procedures versus those which include hysterectomy in the treatment of POP. Hysteropexy procedures may be associated with a shorter operative time and fewer visceral injuries. This is consistent with older analyses.